Analysis of the Islamic Concept of Supervision - Jumiati, Jumiati; Sri Mulyani; Robi Yanto; Imron; M. Anasrul; Kasinyo Harto; Mardiah Astuti (The Future of Education Journal, 2024)
This study aims to analyze the concept of supervision in Islamic education, focusing on its understanding and implementation to improve the quality of education through professional guidance for educators. The method used in this research is literature review, which involves gathering and analyzing written sources relevant to the research topic. The results of the study show that Islamic educational supervision can be understood as a form of professional guidance that provides opportunities for teachers to develop, improve, and enhance the quality of classroom teaching. This supervision emphasizes Islamic values, not only as a tool to monitor or assess teacher performance but also as an effort to encourage the holistic development of teachers' competencies, both in technical teaching aspects and in the development of character and spirituality. Islamic educational supervision aims to help educators improve their performance by emphasizing harmonious relationships between superiors and subordinates, as well as improving the quality of teaching and learning based on religious values. Therefore, this supervision is not only focused on administrative or managerial aspects but also serves as an integral process in shaping the professionalism and character of educators in accordance with Islamic teachings, which in turn will have a positive impact on the overall quality of education.